1995
DOI: 10.2151/jmsj1965.73.2b_267
|View full text |Cite
|
Sign up to set email alerts
|

4-5-Day-Period Variation and Low-Level Dry Air Observed in the Equatorial Western Pacific during the TOGA-COARE IOP

Abstract: A significant 4-5-day-period variation was observed in surface and aerological data obtained at the equator, 156E during November 1992. The time-height structure of the variation is determined by use of spectral and composite analysis. The 4-5-day period variation can be basically explained by westward-propagating mixed Rossby-gravity wave disturbances. However, the structure of the circulation was significantly distorted by the presence of a tropical depression. Further, two distinctive events of extremely dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
70
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 9 publications
11
70
0
Order By: Relevance
“…In order to investigate the origin of the dry air masses, we calculated Lagrangian backward air parcel trajectories for all very dry sounding cases listed in Table 4 using NCEP/ NCAR reanalysis data sets, and following the previous works of Numaguti et al (1995) and Yoneyama and Parsons (1999). Calculations were started from 700 hPa and linear interpolation was used for both time and space.…”
Section: Air Parcel Trajectoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to investigate the origin of the dry air masses, we calculated Lagrangian backward air parcel trajectories for all very dry sounding cases listed in Table 4 using NCEP/ NCAR reanalysis data sets, and following the previous works of Numaguti et al (1995) and Yoneyama and Parsons (1999). Calculations were started from 700 hPa and linear interpolation was used for both time and space.…”
Section: Air Parcel Trajectoriesmentioning
confidence: 99%
“…They concluded that this bimodality resulted from the frequent occurrence of extremely dry air intrusions from higher latitudes into the basically moist tropical environment. Since the warm pool had been considered to be perpetually in the moist conditions with the knowledge before TOGA COARE, the dry intrusion event has attracted many researchers in studying the mechanism, and its impact on moisture variability (e.g., Parsons et al 1994;Numaguti et al 1995;Yoneyama and Fujitani 1995;Sheu and Liu 1995;Mapes and Zuidema 1996;DeMott and Rutledge 1998;Yoneyama and Parsons 1999;Parsons et al 2000;Redelsperger et al 2002). Yoneyama and Parsons (1999) showed that these lateral intrusions were associated with mid-latitudes breaking Rossby waves.…”
Section: Introductionmentioning
confidence: 99%
“…4 resembles the case analyzed by Numaguti et al (1995), in that the dry air appeared associated with the @5-dayperiod meridional wind variation. To investigate the large-scale structure responsible for the 5-dayperiod variation in the wind and humidity, the NCEP/NCAR global objective analysis data in the observation period was examined.…”
Section: Equatorial Rossby Wavementioning
confidence: 61%
“…Frequent appearances of extremely dry air in the lower and mid troposphere over the tropical western Pacific Ocean, first recognized in the TOGA COARE IOP data sets, has received a great deal of attention (e.g., Parsons et al 1994;Numaguti et al 1995;Yoneyama and Fujitani 1995;Mapes and Zuidema 1996; Johnson et al 1996;Sheu and Liu 1995;DeMott and Rutledge 1998;Yoneyama and Parsons 1999;Parsons et al 2000). The formation of the dry layer cannot be explained by vertical adiabatic displacements near the trailing edge of mesoscale convective systems.…”
Section: Equatorial Rossby Wavementioning
confidence: 99%
See 1 more Smart Citation